The influence of iron losses on selecting the minimum excitation capacitance for self-excited induction generator (SEIG) with wind turbine - Hayder Hussein Kadhum; Ahmed Samawi Alkhafaji; Hayder H.Emawi H. Emawi (Institute of Advanced Engineering and Science, 2020)
The capacitance selection of the three-phase self-excited induction generators (SEIG) driven by wind energy is influences by the iron losses. This paper is dealing with this problem by constructing a steady state model of the generator supplying an induction oil pump. No previous literature studying the requirements of selecting the minimum excitation capacitance under the iron loss impact is found. This work is focusing on: (i) a novel evaluation of the characteristics of the induction generator taking iron loss into account. (ii) the errors caused by neglecting the iron loss. (iii) the importance of including the iron-loss in any accurate analysis. (iv) the errors occurred in the selection of the precise excitation capacitance (Cexct) when the iron-loss neglected. Nodal analysis is suggested to describe the study-state performance of the proposed model. A Matlab/simulation is established to validate the proposed model.